PTH-044 Poor sleep quality in irritable bowel syndrome: a comparison with healthy adult controls. (23rd September 2015) - Sisson, G; Junghans, C; Bjarnason, I
Abstract : Introduction: Irritable bowel syndrome (IBS) is a common disorder resulting in a wide range of abdominal and bowel symptoms which often have an impact on quality of life (QOL). Poor sleep quality also affects QOL and is a recognised feature of inflammatory bowel disease as well as other medical and psychiatric disorders.1 2 Although poor sleep quality is reported in IBS little is known about its prevalence. Here we compare sleep quality in IBS with health controls using the Pittsburgh Sleep Quality Index (PSQI) a standardised and validated quantitative measure of sleep quality.1 Methods: Consecutive patients with a diagnosis of IBS attending the outpatient gastroenterology department of Kings College Hospital were recruited. Healthy controls were recruited from hospital staff and students on a voluntary basis. All patients and controls gave informed written consent. Exclusion criteria were night shift work, current or past sleep disorder, inflammatory bowel disease (IBD) or other significant health problem that may affect sleep (IBS was excluded from the control group). All patients completed the a health and life style questionnaire and a PSQI which gives a quantitative sleep quality score from 1 to 21 with a higher score representing a worse sleep quality. Cases and controls were compared using the Mann–Whitney U test in Stata 8 statistical software. Results: A total of 90 subjects, 63 patients and 27 controls were recruited. The mean PSQI was 9.6 and 4.4 in IBS and control subjects, respectively (CI 8.6 to 10.7 and 3.5 to 5.4). (p<0.0001). Conclusion: This study is the first to demonstrate and quantitate poor sleep quality in patients with IBS when compared to healthy controls. Poor sleep quality appears to be yet another manifestation of the multi-organ involvement of the disease and may add further to the reduced QOL seen in IBS.